Organ‐on‐Chip Recapitulates Thrombosis Induced by an anti‐CD154 Monoclonal Antibody: Translational Potential of Advanced Microengineered Systems. Issue 6 (30th April 2018) - Barrile, Riccardo; van der Meer, Andries D.; Park, Hyoungshin; Fraser, Jacob P.; Simic, Damir; Teng, Fang; Conegliano, David; Nguyen, Justin; Jain, Abhishek; Zhou, Mimi; Karalis, Katia; Ingber, Donald E.; et al.
Abstract : Clinical development of Hu5c8, a monoclonal antibody against CD40L intended for treatment of autoimmune disorders, was terminated due to unexpected thrombotic complications. These life‐threatening side effects were not discovered during preclinical testing due to the lack of predictive models. In the present study, we describe the development of a microengineered system lined by human endothelium perfused with human whole blood, a "Vessel‐Chip." The Vessel‐Chip allowed us to evaluate key parameters in thrombosis, such as endothelial activation, platelet adhesion, platelet aggregation, fibrin clot formation, and thrombin anti‐thrombin complexes in the Chip‐effluent in response to Hu5c8 in the presence of soluble CD40L. Importantly, the observed prothrombotic effects were not observed with Hu5c8‐IgG2σ designed with an Fc domain that does not bind the FcγRIIa receptor, suggesting that this approach may have a low potential risk for thrombosis. Our results demonstrate the translational potential of Organs‐on‐Chips, as advanced microengineered systems to better predict human response.